If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=2(m-16)
We move all terms to the left:
2-(2(m-16))=0
We calculate terms in parentheses: -(2(m-16)), so:We get rid of parentheses
2(m-16)
We multiply parentheses
2m-32
Back to the equation:
-(2m-32)
-2m+32+2=0
We add all the numbers together, and all the variables
-2m+34=0
We move all terms containing m to the left, all other terms to the right
-2m=-34
m=-34/-2
m=+17
| 7+7b–2–15b+b=4b–5–11b+2+10 | | 2(3x–1)=-6x–2 | | 7x+8+2x-3=5x+7+4x-3 | | 17^-x+4=2^-7x | | 3(7x+5)=2 | | D=13x+15 | | -8d+-7d=15 | | 52=10x+7 | | 59+x=90 | | 10x-2=4(-x-10) | | 8e=36 | | 3g-7g=-4 | | 1/3(x+3)=12 | | 7-2-1/7-3x/7=2x/3-1/3 | | 3x-7-(9x-6)=15 | | 8b+8b=–12 | | 915=1500-35x | | 12k-8k=16 | | Xx3/8=-15/32 | | 7+n×2=20 | | -4=-4(r-19) | | 24=3+(x-1)2 | | √x+√x+8=2√x | | 8(y+2)=5(2y-4) | | 4(6x-1)^2-5=223 | | 4^3x-1=32 | | -4(m+12)=-8 | | .4x+56=60 | | 10=z−2+7 | | -3b=-11=-2 | | 9(x-1)-1=4x+5(-3+x) | | 3p-6+6=5{p+4} |